OPTIMALISASI KUALITAS LAYANAN SDM AKAN KEPUASAN PELANGGAN PADA UMKM BAKPIA WONG JOGJA - Ghoni, Ahmad; Latif, Latif; Bugis, Meili (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service activity aims to optimize the quality of human resource (HR) services to increase customer satisfaction in Bakpia Wong Jogja MSMEs. The main problem faced by partners is the lack of understanding and skills of employees in providing excellent service to customers, which has an impact on low levels of customer satisfaction and loyalty. The methods used in this activity include training, mentoring, and periodic evaluation of the implementation of customer service standards. The results of the activities showed a significant improvement in employee attitudes, communication skills, and speed of service. In addition, there has been a positive increase in customer feedback regarding the shopping experience at Bakpia Wong Jogja. With the optimization of human resources services, partner MSMEs are able to build a competitive advantage and strengthen their position in the local market. This activity is expected to be a model for human resource empowerment for other MSMEs in an effort to increase customer satisfaction in a sustainable manner